Optimization and tribological properties of semi metallic friction materials / Aznifa Mahyam Zaharudin - Zaharudin, Aznifa Mahyam (Institute of Graduate Studies, UiTM, 2017)
The main goal of this work presented in this thesis was to study the tribological properties of newly formulated semi-metallic friction material under different manufacturing parameters, material constituents and friction test parameters. In the first category, the optimization of manufacturing parameters (molding pressure, molding temperature and molding time) for producing the friction materials using powder metallurgy technique were investigated. The optimum manufacturing parameters were determined using Taguchi method where coefficient of friction (COF) and thickness loss were selected as the quality target. These optimal parameters were 500 kN molding pressure, 150oC molding temperature, and 600 seconds molding time. The results revealed that high molding pressure and temperature do not compulsorily produce the best performance in tribological properties. It could be explained by degradation of the resin structure and the loss of binding properties. The investigation also found that adequate molding time was required for sufficient binding of the tested materials. It was also observed that molding pressure has the strongest effect on physical and tribological properties. High molding pressure may cause the binder to separate from the brake friction material, thus less binder to hold the powder particles in the matrix. In the second category, a study was performed to investigate the effect of phenolic resin, rubber, calcium carbonate and graphite on the tribological properties. The samples were prepared under optimum manufacturing parameters…